2019
DOI: 10.1002/elan.201900252
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric Immunosensor for Rapid Detection of Honeybee Pathogen Melissococcus Plutonius

Abstract: European foulbrood (EFB) is a honeybee larvae disease caused by a bacterium Melissococcus plutonius. An amperometric immunosensor based on a sandwich assay was developed for rapid point‐of‐care detection of this pathogen. An in‐house made anti‐Melissococcus antibody was immobilized to a gold surface of a screen‐printed sensor via self‐assembled monolayer of cysteamine activated with glutaraldehyde. The direct impedimetric detection of captured microbial cells was tested, however, a better performance was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Polachova et al [ 23 ] recently developed a highly sensitive up-conversion-linked immunosorbent assay (ULISA) that employs photon-up-conversion nanoparticles (UCNPs) for the detection of M. plutonius using polyclonal antibodies made in house. Biosensors have also recently been established in laboratory diagnostics [ 24 , 25 ]. The routine use of immune-based techniques is limited, however, because they require EFB specific antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Polachova et al [ 23 ] recently developed a highly sensitive up-conversion-linked immunosorbent assay (ULISA) that employs photon-up-conversion nanoparticles (UCNPs) for the detection of M. plutonius using polyclonal antibodies made in house. Biosensors have also recently been established in laboratory diagnostics [ 24 , 25 ]. The routine use of immune-based techniques is limited, however, because they require EFB specific antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the LODs achieved in the complex matrices of homogenized bees and larvae were 2.4 × 10 5 and 7.0 × 10 5 CFU mL −1 , respectively. It is reported that negative control of P. alvei confirmed the high selectivity of such immunoassay [ 36 ]. Another study reported on the use of polyimide sheet modified with carbon and AuNPs inks through flexographic printing technique and drop casted with glucoseoxidase (5 μL, Gox, 7 × 10 9 pg/mL) for chronoamperometry detection of 26 μM glucose mutarotated in DI water for 24 h [ 37 ].…”
Section: Electrochemical Immunosensorsmentioning
confidence: 81%
“…This method is based on the measurement of a current flow that relates to the concentration of a measured analyte such as a pathogen. The amperometric platform applies a constant potential at the working electrode related to the reference electrode, where the potential is obtained from the electrochemical oxidation or electroreduction of an electroactive species [48,49]. This system has several advantages, including low costs and sensitivity.…”
Section: Amperometric Platformmentioning
confidence: 99%